Fabrication of titanium bipolar plates for proton exchange membrane fuel cells by uniform pressure electromagnetic forming. (11th November 2021) - Dong, Pengxin; Li, Zhangzhe; Feng, Sheng; Wu, Zelin; Cao, Quanliang; Li, Liang; Chen, Qi; Han, Xiaotao
Abstract: Electromagnetic forming (EMF) is a type of noncontact and high-speed forming process that offers several advantages, such as high material formability, low springback, and low die cost. In this study, titanium bipolar plates (BPPs) for proton exchange membrane fuel cells are fabricated by EMF using a uniform pressure actuator that provided a uniform pressure distribution and high efficiency. A three-dimensional coupled electromagnetic-mechanical simulation model is established to optimize the dynamic forming process. Simulation results show that the channel depth is proportional to the impact velocity of the titanium workpiece. A forming window is established as a design guideline. Finally, a titanium BPP with sufficient channel depth (0.4 mm), high aspect ratio (0.67), low thinning rate (not exceeding 15.89%) and high corrosion resistance is successfully fabricated at a velocity of 286 m/s, thereby demonstrating that EMF is a feasible process for fabricating titanium BPPs. Graphical abstract: Image 1 Highlights: Fabrication of titanium bipolar plate by uniform pressure electromagnetic forming. The impact velocity of the workpiece is almost proportional to the channel depth. The forming velocity of the workpiece can reach about 300 m/s. The channel depth of the TA1 bipolar plate can reach 0.4 mm (0.67 aspect ratio). The thinning rate in the thickness of the TA1 bipolar plate is less than 15.89%.